Capital Dynamics and Sustainable Growth in Six ASEAN Nations: GMM Estimation in The Perspective of SDGs - Mubarrok, Wafiyulloh; Purna, Fitra Prasapawidya; Chauhan, Rahul; Fitrianingsih, Arina (Universitas Negeri Yogyakarta, 2026)
Sustainable economic development in Southeast Asia remains a central theme in regional policy debates, particularly regarding the efficiency of factor accumulation. This study empirically investigates the dynamic relationship between physical capital, human capital, labor force, and economic growth in six ASEAN countries (Indonesia, Vietnam, the Philippines, Cambodia, Laos, and Myanmar). Using a Two-Step System Generalized Method of Moments (GMM) approach for the period 2017–2023, the study overcomes potential endogeneity issues and captures the path-dependent nature of regional growth. Empirical results demonstrate a high degree of growth persistence, with the lagged GDP coefficient indicating a strong momentum effect. Physical capital is found to be the primary and most significant driver of economic expansion, validating the importance of sustained infrastructure investment. In contrast, human capital and labor force participation do not have a statistically significant impact on GDP, highlighting the profound